Rethinking the frontiers of vaccine acceptance: Impact of visual messages in promoting the actual intake of COVID-19 vaccines among vulnerable populations - Ngozi Agujiobi-Odoh; Itiav Vershima Joseph; Chinweobo-Onuoha Blessing; Chidi Amaechi; Obinna Muoh; Peter Nwokolo; Gever Verlumun Celestine (Taylor & Francis Group, 2023)
Studies on COVID-19 vaccine mainly focused on behavior intention and rarely on actual intake. This study attempted to fill this gap by assessing the impact of visual artistic messages on COVID-19 vaccination among victims of insecurity. The study was a quasi-experiment involving 362 victims of insecurity. There were two groups in the quasi experiment known as control and treatment groups. The former did not receive the intervention while the latter did. The results of the study revealed that vaccination among the participants in the visual intervention improved from 12% before the visual intervention to 74% after the intervention and 95% after 6 months of follow-up assessment. On the contrary, COVID-19 vaccination for the no visual intervention only slightly improved from 13% to 18% and 19%, respectively, within the same time framework. The study expands the argument on security discourse by highlighting the need to consider the health welfare of victims of armed conflict as part of the larger security discourse. Doing so will not only improves existing literature but also provides the needed empirical data that will guide policies and program on security issues. Theoretically, the study has offered fresh understanding regarding variables from the health belief model, such as perceived severity and perceived vulnerability.